2020
DOI: 10.1245/s10434-020-08825-8
|View full text |Cite
|
Sign up to set email alerts
|

The Use and Benefit of Adjuvant Radiotherapy in Parathyroid Carcinoma: A National Cancer Database Analysis

Abstract: Background. The routine use of external beam radiotherapy (EBRT) is not recommended for parathyroid carcinoma (PC). However, case series have demonstrated a potential benefit in preventing local recurrence with EBRT. We aimed to characterize the patient population treated with EBRT and identify any impact of EBRT on overall survival (OS) in parathyroid carcinoma. Methods. Patients who underwent surgery for PC from 2004 to 2016 were identified from the National Cancer Database. Clinicopathologic variables and O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 25 publications
2
25
0
Order By: Relevance
“…1 e, f) [ 8 ]. Chemotherapy and/or radiotherapy are largely ineffective, and the 10-year survival rate is around 50–70% [ 22 ], with death often due to hypercalcemia. Morbidity due to complications following repetitive neck surgery (hypoparathyroidism, recurrent nerve palsy) is also high [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…1 e, f) [ 8 ]. Chemotherapy and/or radiotherapy are largely ineffective, and the 10-year survival rate is around 50–70% [ 22 ], with death often due to hypercalcemia. Morbidity due to complications following repetitive neck surgery (hypoparathyroidism, recurrent nerve palsy) is also high [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…According to our experience and recent studies, radical surgical approach is currently the goal standard of treatment for recurrences [ 3 , 39 , 40 , 42 , 45 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…In fact, according to literature, only a few authors [ 48 – 54 ] attest the usefulness of radiotherapy and chemotherapy in improving rate of recurrence and survivor but the efficacy of adjuvant therapies has recently been disappointed in the management of recurrent parathyroid carcinoma, even if multicentric studies for improved long-term outcomes are still lacking [ 46 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…The authors reported no significant association between any demographic or pathologic feature and prognosis. A recent National Cancer Database Analysis on 885 patients reported a 5-year and 10-year OS of 85.4% (95% CI 82.4-87.9%) and 67.1% (95% CI 61.7-72.0%) ( 3 ).…”
Section: Discussionmentioning
confidence: 99%
“…The cornerstone of the treatment for PC is surgery. Complete surgical en bloc resection with ipsilateral hemithyroidectomy and prophylactic central lymphadenectomy (level VI) is generally recommended, and microscopic negative margins are considered the best chance for cure ( 2 , 3 , 20 , 23 26 ). Lymphadenectomy of regional lymph nodes other than level VI is not recommended as no therapeutic benefit has been established ( 22 , 27 ).…”
Section: Discussionmentioning
confidence: 99%